PENGARUH PENGGUNAAN MEDIA POP UP BOOK TERHADAP HASIL BELAJAR MATERI BAGIAN TUBUH TUMBUHAN DI KELAS IV SDN 14 BANDA ACEH - Fitriana; Helminsyah; Miswatul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of students in the Natural and Social Science (IPAS) subject, particularly in the plant body parts material in Grade IV SDN 14 Banda Aceh. This was caused by the dominance of lecture-based teaching methods and the minimal use of engaging and interactive learning media, which led students to be passive and less actively involved in the learning process. This study aimed to determine the effect of using Pop Up Book media on student learning outcomes in IPAS plant body parts material in Grade IV SDN 14 Banda Aceh. The study used a quantitative approach with a quasi-experimental design. The sample consisted of 58 students divided into Grade IV A as the experimental class (29 students) and Grade IV B as the control class (29 students). Data were collected through written tests in the form of pretest and posttest. Data analysis used the Independent Samples T-Test after the Shapiro-Wilk normality test. The results showed that the average posttest score of the experimental class was 85.97, while the control class was 62.76. The Independent Samples T-Test showed a t-value of 9.585 with a significance value of 0.000 < 0.05, so the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. It can be concluded that there is a significant effect of using Pop Up Book media on student learning outcomes in IPAS plant body parts material in Grade IV SDN 14 Banda Aceh.